Generalized Proximal ψ-Contraction Mappings and Best Proximity Points - Winate Sanhan; Chirasak Mongkolkeha; Poom Kumam (Abstract and Applied Analysis)
We generalized the notion of proximal contractions of the first and the second kinds and established the best proximity point theorems for these classes. Our results improve and extend recent result of Sadiq Basha (2011) and some authors.